District Nutrition profile: A quick guide - George, Nitya Rachel; Vaid, Abhilasha; Nguyen, Phuong Hong; Avula, Rasmi; Menon, Purnima (International Food Policy Research Institute, 2018)
India is home to millions of undernourished children; however, little is known about the extent of undernutrition and its multiple determinants at the district level. POSHAN has generated District Nutrition Profiles (DNPs) for the 640 districts of India, with the aim of creating awareness, facilitating evidence-based discussions, and mobilizing action for nutrition at the district level. These 4 page profiles present a snapshot of the state of nutrition and its multiple determinants in each district. They were conceptualized to enable local leaders and civil society to understand what it takes to effectively tackle undernutrition in their communities. Data on the nutritional status of children in India is often only available at the national and state levels, with very little data present at the district level. So, this series is a step towards bridging this knowledge gap.